Management of male premature ejaculation: from past to future - Chang, Jiaqing; Zhao, Weiwei; Ma, Lili; Zhao, Juan; Li, Qiming; Wang, Xueyang; Ju, Haichao; Wang, Xinping; Xiping, Xing (Frontiers in Endocrinology, 2025)
Premature ejaculation (PE) is a common disease of the male reproductive system, which seriously affects the quality of life of patients and their partners. Currently, PE is regarded as a biopsychosocial disease with complex etiologies and diverse treatment methods. Oral selective serotonin reuptake inhibitors (SSRIs) are the first-line treatment for PE, with advantages such as high safety, rapid onset of action, and non-invasiveness. However, topical anesthetics, behavioral and psychological therapies, device-assisted treatments, and traditional Chinese medicine (TCM) can also serve as alternative therapies for patients intolerant to SSRIs. With the rapid development of technology, some new methods—such as low-intensity extracorporeal shock wave therapy (Li-ESWT) and transcutaneous electrical nerve stimulation (TENS)—can even improve PE through mechanisms like regulating nerve conduction and improving local microcirculation. These are all important directions for the future treatment of male PE. In this mini-review, we will elaborate on these therapeutic approaches.